Pendidikan Tinggi sebagai Aktualisasi Fitrah dalam Perspektif Wasathiyah - Nashihin, Muhammad; Hakim, Nur; Miftahuddin, Miftahuddin (MADINAH, 2025)
This research aims to examine the meaning of higher education as the path of human nature from the wasathiyah perspective, focusing on its relevance in the context of socio-economic changes in coastal communities. The background of this research is based on the strong patriarchal views that limit the role of women in Higher education, a narrow understanding of destiny, and low participation in Higher education among coastal communities. This research uses a qualitative approach based on a literature study to analyze the concept of higher education as the path of fitrah from an Islamic perspective and its relevance to contemporary issues. The analysis was conducted on primary literature (the Qur'an and hadith) as well as secondary literature in the form of books, articles, research reports, and data from relevant institutions such as BPS, Kemendikbud, and UNESCO. The results show that Higher education is seen as a form of actualization of human nature, which is endowed with the potential of reason, heart, and instinct to develop. The concept of hair and destiny in Islam encourages maximum efforts in studying, including for women and marginalized communities. The findings confirm that Higher education is a strategic necessity in the face of socio-economic changes in coastal communities, which are now affected by the ecological crisis, limited natural resources, and the demands of globalization. This research contributes to enriching the understanding of the importance of Higher education as part of the mission of human creation in Islam. Research recommendations include the need to strengthen educational literacy programs in coastal communities, synergies between pesantren, universities, and local governments, and the development of an inclusive fitrah-based curriculum.